PENGARUH FREE CASH FLOW DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PT. AKASHA WIRA INTERNATIONAL TBK PERIODE 2014-2023 - Yusnita, Indri; Nurwita (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to analyze the influence of Free Cash Flow (FCF) and Company Size (CS) on Earnings Management at PT. Akasha Wira International Tbk over the period 2014-2023. This research employs a quantitative approach with secondary data obtained from the company's financial statements. The analytical method used is multiple linear regression to test the proposed hypotheses. The results show that Free Cash Flow and Company Size have a significant effect on Earnings Management practices. The larger the Company Size, the higher the level of Earnings Management practices undertaken. Additionally, high Free Cash Flow also contributes 67,3% to an increase in Earnings Management practices. This research implies that companies should be more cautious in managing Free Cash Flow and consider Company Size to minimize Earnings Management practices.